THE CONCEPT OF YOUTH IN THE QUR’AN: A STUDY OF YOUTH CHARACTER BASED ON ISLAMIC VALUES - Nurrochim, Zuni (Tanzil: Jurnal Studi Al-Quran, 2025)
This study aims to explore the concept of youth in the Qur’an through a thematic interpretation of five key terms that reflect the characteristics and values associated with young individuals: Aṣḥāb al-Kahfi, ghulāmin ḥalīm, bunayya, fatan/fityah, and dhurriyah. These terms were selected to represent ideal youth traits rooted in Qur’anic teachings. Using a qualitative research method with a thematic tafsir approach, this study systematically analyzes verses of the Qur’an to uncover these terms' deeper meanings and educational implications. The findings reveal that aṣḥāb al-kahfi symbolizes youth who are resilient and curious in their pursuit of truth; ghulāmin ḥalīm highlights gentleness, patience, and compassion; bunayya reflects filial piety and strong moral foundations; fatan/fityah illustrates courage and revolutionary spirit in upholding truth; and dhurriyah emphasizes the significance of nurturing generations that are faithful, morally upright, and spiritually steadfast. The study concludes that the Qur’anic concept of youth encompasses a holistic balance between intellectual competence, moral strength, courageous action, and spiritual resilience. These values are highly relevant for contemporary youth development and character education. The role of parents, educational institutions, and society at large is crucial in internalizing these values to shape youth into individuals of integrity, competitiveness, and positive societal impact.